Rational pharmacotherapy of primary open-angle glaucoma in elderly and senile patients - M.V. Tereshchenko; A.E. Egorov; A.B. Movsisyan (РМЖ "Клиническая офтальмология")
M.V. Tereshchenko1, A.E. Egorov1,2, A.B. Movsisyan1,2 1Hospital for War Veterans No. 2, Moscow, Russian Federation 2Pirogov Russian National Research Medical University, Moscow, Russian Federation Glaucoma is one of the socially significant and disabling diseases highly prevalent worldwide. Population ageing and increase in life expectancy will result in even a bigger growth of glaucoma cases. The main principle of medical management of primary open-angle glaucoma (POAG) is to provide a timely ocular hypotensive therapy directed at lowering intraocular pressure, the only modifiable risk factor in the disease progression, to a target level. The article describes specific approaches to the medical management of elderly and senile patients with POAG, taking into consideration age-related eye problems and medications used for comorbidities. The selection of drugs is based on the assessment of their efficacy, probability of adverse events, dosage frequency, convenience of use and the cost of treatment. For a long time, β-adrenergic blocking agents were considered a first line medication for POAG. However, due to the adverse events, including systemic side effects, β-blockers have become second-line drugs for the treatment of elderly and senile patients. First-line medications now include prostaglandin analogues characterized by a higher efficacy and a lower rate of adverse events. The best option for patients with POAG is the use of preservative-free highly selective prostaglandin analogues which reduce intraocular pressure to a target level, maintain patient’s visual functions for a long time, improve the quality of life and cause significantly less adverse reactions on the ocular surface. Keywords: glaucoma, prostaglandin analogues, β-blockers, dry eye syndrome, preservatives, travoprost. For citation: Tereshchenko M.V., Egorov A.E., Movsisyan A.B. Rational pharmacotherapy of primary open-angle glaucoma in elderly and senile patients. Russian Journal of Clinical Ophthalmology. 2022;22(4):234–239 (in Russ.). DOI: 10.32364/2311-7729-2022-22-4-234-239.